Método ultrasónico para la evaluación de los parámetros de coagulación en la sangre a través del tiempo de protrombina (TP). (2024)
Coagulation is essential for maintaining vascular integrity in the human body, with the measurement of clotting times crucial for monitoring hemorrhagic disorders and assessing the effectiveness of anticoagulant treatments, particularly prothrombin time (PT) for the extrinsic pathway of coagulation. Over the years, ultrasound technology has made significant strides in this field, though challenges remain in understanding the mechanisms and optimizing ultrasound-based measurement systems. The implementation of a clotting time estimation system using ultrasound instrumentation and computational intelligence methods represents a significant advancement in diagnostic medicine. In contrast to invasive and subjective methods, this approach offers a more precise and objective assessment of clotting times, enhancing diagnostic reliability and patient safety by enabling rapid identification of disorders and real-time evaluation of anticoagulant treatments. Consequently, this system serves as a valuable tool for clinical decision-making, promoting advances in processing and computational strategies in the field of coagulation